Chlorpyrifos induces NLRP3 inflammasome and pyroptosis/apoptosis via mitochondrial oxidative stress in human keratinocyte HaCaT cells. (2nd December 2015) - Jang, Yoonjeong; Lee, Ah Young; Jeong, Sang-Hee; Park, Kyung-Hun; Paik, Min-Kyoung; Cho, Nam-Joon; Kim, Ji-Eun; Cho, Myung-Haing
Highlights: Chlorpyrifos generates ROS in HaCaT cells. Chlorpyrifos causes mitochondrial oxidative stress. NLRP3 inflammasome is induced by chlorpyrifos through mitochondrial ROS generation. Mitochondrial ROS is involved in chlorpyrifos-induced pyroptosis and apoptosis. Abstract: Chlorpyrifos (CPF) has been widely used around the world as a pesticide for both agricultural and residential application. Although various studies have reported toxicity and health-related effects from CPF exposure, the molecular mechanism of CPF toxicity to skin has not been well-characterized. The present study determined the potential mechanism involved in skin toxicity of CPF using the HaCaT human skin keratinocyte cell line. After treating to HaCaT cells, CPF triggered reactive oxygen species (ROS) generation and mitochondrial oxidative stress. We focused on NLRP3 inflammasome, known to induce innate immune response. We used mitochondrial ROS (mROS) scavenger mitoTEMPO to demonstrate a role for mROS in NLRP3 inflammasome and programmed cell death induced by CPF. Our results showed that CPF provoked NLRP3 inflammasome and pyroptosis/apoptosis via an increase of mROS in HaCaT cells. This study proposes that CPF induces innate immune response and skin inflammation through activating the NLRP3 inflammasome in skin epithelial cells. CPF may lead to cutaneous disease conditions and antioxidants could be proposed for therapy against skin exposure to CPF.